2013
DOI: 10.1021/ol4006294
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hydroxymethylation Reactions of Iodoarenes Using CO and 1,3-Dimethylimidazol-2-ylidene Borane

Abstract: A hydroxymethylation reaction of a variety of iodoarenes proceeded effectively in the presence of CO, NHC-borane, diMeImd-BH3 (2) as a radical mediator, and a catalytic amount of AIBN. The reaction took place chemoselectively at the aryl-iodine bond but not at the aryl-bromine and aryl-chlorine bonds. A three-component coupling reaction comprising aryl iodides, CO, and electron-deficient alkenes also proceeded well to give unsymmetrical ketones in good yields. Control experiments show that 2 would act as a hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…On the basis of these preliminary results, and those of previous studies, 6,[9][10][11] we propose the mechanism shown in Scheme 3. Initially, photoexcitation of Eosin Y by visible light generates excited [Eosin Y*].…”
supporting
confidence: 75%
“…On the basis of these preliminary results, and those of previous studies, 6,[9][10][11] we propose the mechanism shown in Scheme 3. Initially, photoexcitation of Eosin Y by visible light generates excited [Eosin Y*].…”
supporting
confidence: 75%
“…Bromides and chlorides do not react under these conditions, the atom-transfer step being likely too slow in such cases. Aryl iodides 87 may also be involved in a similar reaction, but using NHC-boranes (e.g., 88) as a hydrogen donor (2) [61]. The latter are more convenient than usual borohydrides in this context due to their lower H-donation ability, which prevents the premature reduction of the aryl radical precursor.…”
Section: Alkyl Halide Carbonylationmentioning
confidence: 99%
“…Later on we found that borohydride reagents can also serve as radical mediator delivering hydrogen to the radical centre [14], thus we developed a hydroxymethylation method using Bu 4 NBH 4 and a radical initiator [1517]. Recent work in collaboration with Dennis Curran has revealed that, with the use of NHC-borane [18], hydroxymethylation of aromatic iodides can be attained [19]. All these reactions consist of the combination of radical formylation with CO and ionic hydride reduction by hydride reagents (Scheme 1, reaction 1).…”
Section: Introductionmentioning
confidence: 99%